A Study of Preferred Learning Time of Online Learner in Multimedia Microlearning in Higher Education Context - Leong, Kelvin; Sung, Anna; Au, Robin; Lee, Ching (Online Journal for TVET Practitioners, 2022)
This study aims to explore when would online learners prefer to interact with multimedia microlearningâ€ in higher education context. Although microlearning is an emerging topic, most of the previous studies were focus on reporting the application results of microlearning, only very few of previous works were specifically conducted on discussing when would online learners prefer to interact with multimedia microlearning. Total population sampling approach was adopted and questionnaire was used to collect primary data. In total, 77 participants attempted the survey, the response rate is 32.6%. The findings from this study indicate that more learners prefer to study during morning or afternoon time rather than evening or midnight time (H2) (p<0.05). On the other hand, there is no significant difference on when to attempt assessment (H1) and on gender issue (H3, H4). The findings from this study generates knowledge to fill the research gap in the field of microlearning. According to the researcherâ€™s best knowledge, this is the first time that a study like this had been conducted to review and discuss the online learnersâ€™ preferences on interacting multimedia learning. Hopefully, this study could shed some lights on future directions of the development of microlearning.